Design formulation of freshwater fish feed from palm kernel cake (PKC) - Mohd Fakaruddin, Abdul Rahman (2010)
This study is about design formulation of freshwater fish feed from palm kernel cake (PKC). The objectives in this study are to study the nutrition composition of PKC based feed for freshwater fish, to evaluate the palm kernel cake (PKC) used as a possible substitute for soybean meal, corn meal and in an attempt to reduce the impact of rising costs to feed freshwater fish and to determine the appropriate percentage of PKC, and other raw materials for the formulation of feed. There are 3 sample of fish feed (100 gram for each sample) are prepared where the different between of each sample is only the variety percentage of PKC and soybean used. Composition of palm kernel cake (PKC) and final design feed are analyzed by using Near-Infrared Analyzer (NIR). Based on the result, the percentage of protein, fiber and fat from palm kernel cake (PKC) is moderate and acceptable which is suitable used as ingredient in fish feed and the nutrient composition inside the all designed feed is similar or within the range to the standard pellet feed. The sample 2 is the preferable formulation as it used the maximum amount of PKC (30%) and minimum soybean and it can cut off the costing of fish feed.